Heuristic Reflection for Teachers for Better Learning Teaching Interaction - Rosalia Hening Wijayanti (Universitas Sanata Dharma, 2015)
A reflection on teaching is a way to maintain and improve teachers‘ competence which is officially required. One of the reflection sessions to conduct is the end-meeting reflection. The reflection helps teachers evaluate their teaching practice which has been done to confirm the accomplishment of lesson objectives and to improve their future teaching quality. However, the absence of reflection activity occurs not due to the lack of awareness about the importance of reflection, but mainly because of the administrative work load and the tight teaching schedule. Therefore, the researcher aims to propose a reflection model to conform teachers‘ insufficient time in doing a reflection. The theories of reflection and the feedback from practitioners underlie the proposed heuristic five-minute end-meeting reflection model which can be done at the junior high school level.